2017
DOI: 10.2147/ott.s122009
|View full text |Cite|
|
Sign up to set email alerts
|

Fibronectin 1 promotes migration and invasion of papillary thyroid cancer and predicts papillary thyroid cancer lymph node metastasis

Abstract: Lymph node metastasis (LNM) is common in papillary thyroid cancer (PTC), and is an indicator of recurrence. The detailed molecular mechanism of LNM in PTC has not been well described. This study aimed to investigate the role of fibronectin 1 in PTC LNM and its clinical relevance. The expression of fibronectin 1 was confirmed in PTC tissues and cell lines. A correlation analysis was conducted and a receiver-operating characteristic curve obtained. The effect of fibronectin 1 on the proliferation of PTC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…MiR-101-3p has been found to be sponged by lncRNA-MALAT1 and therefore resulted in decreased apoptosis rate of cisplatinresistant lung cells [10]. Another study proposed that NEAT1 inhibited the expression of miR-101-3p and reversed irradiation-resistance in nasopharyngeal carcinoma, which was similar to our study [11]. There are no studies that have been published on the effects of miR-101-3p on RAI resistance of PTC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…MiR-101-3p has been found to be sponged by lncRNA-MALAT1 and therefore resulted in decreased apoptosis rate of cisplatinresistant lung cells [10]. Another study proposed that NEAT1 inhibited the expression of miR-101-3p and reversed irradiation-resistance in nasopharyngeal carcinoma, which was similar to our study [11]. There are no studies that have been published on the effects of miR-101-3p on RAI resistance of PTC.…”
Section: Discussionsupporting
confidence: 89%
“…FN1 was demonstrated as a promising target of miR-101-3p. A previous study revealed that FN1 promoted cell EMT and chemoresistance in breast cancer [11], implying its role in enhancing chemoresistance. In the study, we discovered that the expression level of FN1 was enhanced by miR-101-3p deficiency, which therefore promoted the RAI-resistance of PTC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…TIMP-1, acts as an inhibitor for MMP9 expression that is often co-expressed with this molecule in thyroid tumors and serves as a reliable surrogate marker for BRAF-mutated status and likely aggressiveness (41). Notably, TIMP-1 serves as a prominent PPI hub gene in the Cytoscape network built upon co-expression of TNFRSF12A and CHI3L1, along with LGALS3, a specific biomarker of well-differentiated thyroid carcinomas (42), CXCL16, which mediated the involvement of macrophages in the invasion of papillary TCs (43) and fibronectin, an EMT biomarker which promoted migration and invasion of papillary thyroid cancers (44).…”
Section: Multiple Linear Regression Mega-analysis Results Analysis Fomentioning
confidence: 99%
“…It has been reported that FN1 is upregulated in several tumors such as nasopharyngeal carcinoma (31) and melanoma (32). Upregulation of FN1 indicates poor prognosis in thyroid cancer and nasopharyngeal cancer (33,34). A previous study demonstrated that FN1 may be a potential biomarker for radiotherapy and drug resistance in head and neck squamous cell carcinoma (35).…”
Section: Discussionmentioning
confidence: 99%